2016
DOI: 10.1038/s41522-016-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms and the human skin microbiome

Abstract: The human skin microbiome plays an important role in both health and disease. Microbial biofilms are a well-characterized mode of surface-associated growth, which present community-like behaviors. Additionally, biofilms are a critical element in certain skin diseases. We review how the perception of the resident skin microbiota has evolved from the early linkages of certain microbes to disease states, to a more comprehensive and intricate understanding brought on by biofilm and microbiome revelations. Rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 82 publications
(87 reference statements)
0
83
0
1
Order By: Relevance
“…). Furthermore, it has been shown that interactions between C. acnes and other bacteria, for example S. epidermis , are important for skin health …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…). Furthermore, it has been shown that interactions between C. acnes and other bacteria, for example S. epidermis , are important for skin health …”
Section: Discussionmentioning
confidence: 99%
“…One form of intramicrobial communication is robust quorum sensing and establishment of biofilms. Biofilm formation is critical in skin disease, where precise microbe–microbe network‐based inputs present differential physiological signalling, rendering biofilms untreatable and antibiotic‐resistant . It has been shown that C. acnes form biofilms in follicles in some patients with acne, leading to the hypothesis that an enriched presence and biofilm‐based activity of C. acnes lead to homeostatic imbalance of the microbiota.…”
Section: Human Skin Microbiota: Commensal To Harmfulmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical microbiological and dermatological studies have reproducibly pointed to the strong association between P. acnes and acne vulgaris, 352 between S. aureus and atopic dermatitis, and between Malassezia species and seborrheic dermatitis. 86,352 The advent of NGS technology, as applied to research on the microbial communities of the skin, has led to further information about the microbial biofilm nature of certain skin diseases that were difficult to analyze using classical microbial techniques. In atopic dermatitis, for example, a decrease in microbial diversity was discovered in the lesions.…”
Section: Skin Diseases and The Microbiomementioning
confidence: 99%